A Multidisciplinary Comparison of Different Techniques Among Skilled Water Treaders - van Duijn, Tina; Button, Chris; Masters, Rich S. W. (Frontiers in Physiology, 2021)
In an immersion incident, a person may be required to tread water for extended periods of time in order to survive. Treading water, or maintaining a stable head position above the water surface, can be achieved in several different ways. Determining which treading water techniques are economic (energetically and cognitively) is an important first step in approaching evidence-based water safety instruction. The present study investigated the cognitive and metabolic demands associated with four main techniques for treading water in experienced water treaders. Skilled water treaders (n=21) performed four common treading techniques for 3min each: “running” in the water, “flutter kick” with hands sculling, “upright breaststroke,” and “egg-beater.” Self-reported rate of perceived exertion (RPE) and task load index (TLX) score, as well as objective measures of probe reaction time (PRT; i.e., response to auditory cues while treading), oxygen consumption and heart rate were assessed. The “egg-beater” technique and the “upright breaststroke” technique were linked to significantly lower cognitive and energetic demands compared to the other techniques (VO2: p<0.001 – “Running” M=29.02, SD=7.40/“Flutter kick” M=29.37, SD=8.56, “Breaststroke” M=23.47, SD=7.28, and “Eggbeater” M=23.18, SD=6.31). This study lays the groundwork for future research that may establish the ideal movement behavior in drowning situations and investigate movement instruction to less experienced treaders.